2012
DOI: 10.7166/23-3-520
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Relevance of Technology-Related Variables to the Competitiveness of Small - To Medium-Sized Furniture Manufacturers

Abstract: SMMEs can make a critical and positive economic contribution to South Africa, and small-to medium-sized furniture manufacturers (SM/FMs) have the potential to contribute to economic growth, job creation, and GDP. However, the furniture industry has not stayed abreast of technological advances. To survive in an environment of increasing competition and imports, competitive strategies must be devised. One such strategy is for technology adoption and implementation that can provide solutions for the furniture ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The results imply that the higher the technology level, the more significant the benefits to the business [60].…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…The results imply that the higher the technology level, the more significant the benefits to the business [60].…”
Section: Resultsmentioning
confidence: 68%
“…This study found a strong association between business strategy, technology application, technology purchasing strategy, technology information sourcing, and competitiveness (as measured by business performance and technology-competitive advantage) [60].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations